BOOK REVIEW: Cosmin Popa, “Intelectualii lui Ceausescu si Academia de Stiinte Sociale si Politice (1970-1989)” – “Ceausescu's Intellectuals and the Academy of Social and Political Sciences (1970-1989)”, Editura Litera, București, 2019, 352 p. - BRAEȘ, Mădălina (Studia Universitatis Babeș-Bolyai Historia, 2019)
The volume “Ceausescu's Intellectuals and the Academy of Social and Political Sciences (1970-1989)” written by the researcher Cosmin Popa, edited by the Litera Publishing House in 2018, is a work that provides an overview of how the policies of the past have affected universities` life, respectively the elite of the time. What we can notice in the volume proposed for reviewing is the author's objective perspective on the motivation behind the creation of Nicolae Ceausescu's Academy of Social Sciences and Politics, a tool that would act in the interests of the communist system and propaganda.